Sustainable tourism. Part A : balancing conservation and progress in a dynamic industry - Sharma, Disha; Abdullah, Hamid; Singh, Pramendra (Emerald Publishing Limited, 2024)
In today's world, where the implications of climate change and environmental degradation are becoming increasingly evident, the tourism industry faces a pressing need to address its environmental footprint. Additionally, the rapid growth of tourism in many regions has raised concerns about cultural authenticity and community welfare. Sustainable Tourism, Part A: Balancing Conservation and Progress in a Dynamic Industry aims to provide a comprehensive resource that equips stakeholders in the tourism industry with knowledge and insights to foster sustainable practices. Bringing together diverse perspectives, including those of destination managers, policymakers, tour operators, local communities, and travellers Sustainable Tourism fosters a collective understanding of sustainability in tourism and inspires a shared commitment towards responsible tourism practices. The ultimate goal of Sustainable Tourism is to empower the industry to achieve a harmonious balance between conservation and progress, ultimately forging a responsible and resilient tourism sector that caters not only to contemporary travellers but also safeguards the well-being of future generations.
Keywords: Sustainable tourism.; Ecotourism.; Tourism -- Technological innovations.; Travel, Special Interest, Ecotourism.; Travel guides: eco-tourism, green tourism.; elektronické knihy; electronic books